2014
DOI: 10.1002/jmri.24572
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using 3D MR elastography to determine pancreatic stiffness in healthy volunteers

Abstract: Purpose To evaluate the feasibility of using 3D Magnetic Resonance Elastography (MRE) to determine the stiffness of the pancreas in healthy volunteers. Materials and Methods Twenty healthy volunteers underwent 1.5-T MRE exams using an accelerated echo planar imaging (EPI) pulse sequence with low-frequency vibrations (40 and 60 Hz). Stiffness was calculated with a 3D direct inversion algorithm. The mean shear stiffness in five pancreatic subregions (uncinate, head, neck, body and tail) and the corresponding l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 20 publications
7
125
2
1
Order By: Relevance
“…While there have been several reports in the literature confirming the high reproducibility of MRE derived liver stiffness values on the same subject performed at different times points, these studies were all performed on the same vendor platform [21,22]. To our knowledge, there have been no reports in the literature demonstrating reproducibility of MRE derived liver stiffness values on the same individual on different platforms.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been several reports in the literature confirming the high reproducibility of MRE derived liver stiffness values on the same subject performed at different times points, these studies were all performed on the same vendor platform [21,22]. To our knowledge, there have been no reports in the literature demonstrating reproducibility of MRE derived liver stiffness values on the same individual on different platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo shear stiffness of pancreas was for example investigated with the MR elastography technique (Yin et al, 2008) and found to be 2:070:4kPa which is similar to that of hepatic tissue (Rouviere et al, 2006). Similar investigations were conducted (Shi et al, 2014) with a resulting mean shear stiffness of 1.2 kPa at 40 Hz and 2.1 kPa at 60 Hz, respectively.…”
Section: Introductionmentioning
confidence: 84%
“…Recent preliminary studies with 20 healthy volunteers have suggested the feasibility of three-dimensional pancreatic MR elastography for quantitatively determining the stiffness of the pancreas [53].…”
Section: Mri Studiesmentioning
confidence: 99%